Seed removal and seed dispersal in two selectively-logged forests with contrasting protection levels in Costa Rica - Rosales, Jesús J. (1999)
We evaluated seed removal and the rate of removed seeds (as a measure of dispersal) in two nearby tropical rain forest sites in the Caribbean lowlands of Costa Rica that had been selectively logged buth that differ in their degree of protection from human intrusion (primarily due to hunting) and habitat connectivity: We expected differences between sites in rates of seed removal and the rate of removed seeds, and predicted that secondary seed dispersal rates by mammals would be highest at the protected site. Patterns of seed removal under two protection treatments (semipermeable cages vs. uncaged) varied both within species across sites and within sites across species suggesting site differences in the abundance of vertebrate seed consumers. However, differences were largely species specific. For all species combined, twice as many seeds were dispersed after 50 d of observation at La Selva. We found evidence for differential seed survival in our study species between sites, probably related to altered mammal community composition probably as a result of hunting pressure and loss of habitat connectivity at Tirimbina with respect to La Selva.